Integration of Robotics Service on Guest Experience in Fine Dining Restaurants: A Case of Kileleshwa in Nairobi City County Kenya - Binyanya, Benard (Journal of Hospitality and Tourism Management, 2026)
The hospitality industry has increasingly integrated robotics and artificial intelligence technologies into service delivery to improve operational efficiency, strengthen competitiveness, and enhance guest experiences. This study examined the integration of robotics and artificial intelligence technologies and their influence on guest experiences in fine dining restaurants in Kileleshwa, Nairobi City County, Kenya. Specifically, the study assessed the influence of robotics and artificial intelligence technologies on guest experience and evaluated employees’ reception towards their integration. A descriptive research design was adopted, targeting 37 respondents comprising 25 restaurant employees, including managers, supervisors, waiters, cashiers, receptionists, cooks, and chefs, and 12 guests, including able bodied persons and persons with disabilities. A census approach was used, while data were collected through questionnaires and analysed using percentages, means, and standard deviations. The findings revealed that employees generally received the technologies positively, with 92 percent agreeing that they could work alongside robotic systems and 84 percent reporting improved staff efficiency. All guests agreed that robotics and artificial intelligence technologies improved dining satisfaction through accurate order delivery, while 91.7 percent reported improved meal experiences through timely service. However, most guests continued to value human interaction, with 66.7 percent disagreeing that they preferred robotic interaction to human touch. Acceptance was also lower among elderly guests, while responses concerning the accessibility and user friendliness of robotic systems for persons with disabilities were mixed. The study concludes that robotics and artificial intelligence technologies improve service accuracy, efficiency, restaurant image, and guest satisfaction but cannot fully replace personalised human service. Fine dining restaurants should therefore adopt a hybrid service model, provide employee training, retain human assisted service options, and prioritise accessible technological designs that accommodate guests with diverse abilities and preferences. Keywords: Robotics; Artificial intelligence (AI); Guest experience; PWD guests; Fine dining.